Kontribusi Usaha Kelapa Menjadi Kopra Terhadap Pendapatan Rumah Tangga Petani di Kelurahan Gubukusuma Kecamatan Tidore Utara Kota Tidore Kepulauan - Ilfan Baharuddin; Muhammad Hi. Hasan (Peneliti.net, 2021)
Plantation is the number one business that is mostly cultivated by the people in the City of Tidore Islands. With its geographical location and tropical climate, Tidore is one of the cities with good plantation business development, one of which is coconut plantations. The potential of coconut is so good that it can be developed to improve the community's economy. However, because of this potential, this happens which has not been fully utilized by the community. The conventional method of drying coconuts into copra by the Gubukusuma community is by smoking, of course the results are also different from modern drying which is carried out using a drying machine, the drying system into copra which is carried out using a machine will produce white copra with quality. which is better with a smoking system that produces black or gray copra. Problems that are often encountered by copra coconut farmers who are considered low by copra buyers in the market, departing from the problem of processing coconuts into copra, this is the basis for researchers to conduct research in Gubukusuma Village, namely to find out how much coconut contributes to copra for household income. farmer's ladder. The urgency of the research that the researcher wants to convey from this research is that the local government, especially the Tidore Islands City Government, must strictly monitor the selling price of copra in the market so that there is no price game by copra buyers.